Temporal CT Evaluation of the Relationships between Basic Anatomical Structures and the Round Window: Importance for the Cochlear Implant Surgery - Asal, Neşe; Bayar Muluk, Nuray; Bekin Sarikaya, Pelin Zeynep (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives In the present study, we investigated the round window (RW) and neighboring anatomical structures using temporal computed tomography (CT) which are important for cochlear implant (CI) electrodes.Methods In this retrospective study, the temporal CT images of 112 adult patients (45 males and 67 females) were evaluated. We classified mastoid pneumatization, and measured RW diameter, RW–carotid canal (CC) distance, RW–facial nerve mastoid segment (FNMS) distance, RW–pyramidal eminence distance, RW–jugular bulb (JB) distance, and RW–internal acoustic canal (IAC) distance. Additionally, RW–cochlea angle and RW–facial nerve angle were also measured.Results RW diameters in males were significantly higher than those in females bilaterally (p < 0.05). RW–CC distance and RW–JB distance were both smaller than 10 mm. RW–IAC distance was 2.54 to 2.68 mm, and RW–FNMS distance was 4.20 to 4.40 mm. RW–cochlea angle ranged from 39.62 to 41.91 degrees and RW–FN angle ranged from 17.28 to 18.40 degrees. Males showed better mastoid pneumatization values (p < 0.05). In higher RW diameters, RW–JB distance decreased, and in pneumatized mastoids, RW–JB distance increased. RW–JB distance and RW–CC distance were detected to increase together (p < 0.05).Conclusion RW is crucial anatomic structure for CI surgeries. RW diameters are between 1.21 and 1.35 mm and lower in the females. Males exhibited better mastoid pneumatization values than the females, and CC and JB distances from RW were farther in well-pneumatized mastoids. Future studies should include comprehensive clinical and surgical findings.
Keywords: round window; carotid canal; facial nerve mastoid segment; jugular bulb; RW–FN angle; RW–cochlea angle